A bi-objective manufacturing/remanufacturing system considering downward substitutions between three markets. (January 2021) - Afshar-Bakeshloo, Mohammadbagher; Jolai, Fariborz; Bozorgi-Amiri, Ali
Highlights: Inventory control policy for a hybrid manufacturing/remanufacturing system. A finite number of times for remanufacturing. Substitution between three markets (new/once-remanufactured/twice-remanufactured). Bi-objective MDP considering profit and customer satisfaction. Sales-dependent returns. Abstract: An inventory control problem of a hybrid manufacturing/remanufacturing system under stochastic demand is studied. The paper proposes a successive substitution strategy between prime, budget and low budget segments of a market. Meaning a manufactured product may substitute for a remanufactured product at a discounted rate. The success of this proposal proportionally is dependent on the discount rate. Similarly, a once-remanufactured product may substitute for a twice-remanufactured product. In this proposal, a sales-dependent return is adopted to enhance returns prediction. This tactic utilizes a virtual stock of previous period sales instead of a used product stock. In such arrangements, only a fraction of customers accept keeping and returning their used product at the end of the product's lifetime. This is a push system because as soon as the company makes an order for remanufacturing, a core will be returned by a ready/potential customer and instantly will be pushed into the remanufacturing process. The system is formulated by a bi-objective Markov decision process considering profit and customer satisfaction criteria to provide optimal policy in the form of a lookup table. The heuristic policy is then characterized by utilizing five control parameters. This is a state-dependent threshold policy with a small deviation from the optimality. Then the effects of thresholds are investigated applying DOE and ANOVA. Finally, the performance of the successive substitution strategy using real data from the tire industry is examined. The results show that profitability, serviceability and core acquisition can be improved by using the proposed strategy.